Relative Performance of Trading Halts and Price Limits: Evidence from the Spanish Stock Exchange - Kim,Yong H.; Yague,Jose; Yang,Jimmy (International Review of Economics and Finance, 2008)
We study the relative performance of trading halts and price limits using data from the Spanish Stock Exchange where both mechanisms have coexisted. According to our evidence, trading activity increases after either mechanism is triggered. Volatility stays the same after trading halts but increases after price limit hits. Our evidence also shows that the bid–ask spread is narrower after trading halts but wider after price limit hits. Information is efficiently reflected in stock prices once trading resumes after trading halts, but there is evidence of market overreaction for upper price limits. Our overall result may have important policy implications for financial markets in the world.
Keywords: Finance